Rewiring anaerobic digestion: production of biofuel intermediates and high-value chemicals from cellulosic wastes - Reyes, Jorge L. Rico, author; De Long, Susan, advisor; Sharvelle, Sybil, committee member; Reardon, Kenneth, committee member; Engle, Terry, committee member (Colorado State University. Libraries, 2019)
Anaerobic Digestion (AD) is a mature biotechnology for the valorization of organic residues, and AD is one of the most popular technologies for organic carbon recovery and waste stabilization. Research and applications for this process have been focused on the production of methane-containing biogas. However, the recent drop in natural gas prices has affected the economic value and market for this biofuel. Existing AD applications for the management of organic wastes (municipal and agricultural) are not economically attractive. Furthermore, it is unclear if methane biogas is the most economically advantageous product. Promising opportunities for AD have emerged in the production of chemical intermediates, such as short-chain fatty acids (SCFA). The market for these chemicals is growing, and more sustainable practices could replace their current petrochemical-based production. AD for the production of SCFA is an alternative approach with attractive market and economic opportunities. This approach is known as the carboxylate platform and relies on the beneficial features of using undefined mixed microbial cultures (also known as microbiomes) for fermentation of heterogeneous organic residues. One of the main identified technological barriers to the carboxylate platform is the inability to control the product spectrum and achieve high yields. AD is a complex biological system, and advances in the fundamental understanding of the microbial ecology associated with SCFA production in these systems are still needed. The identification of specific taxonomic groups involved in the synthesis of certain products could provide insights for novel microbial shaping methods (e.g., bioaugmentation) to improve SCFA selectivity and production yield. This study investigated the relationships between the production of SCFA and the microbial composition from three inoculum sources (anaerobic digester sludge, beef cattle rumen, and bison rumen), with cellulose as a carbon source. Results from the present work found associations between specific taxonomic groups within each of the microbial communities, and the production of particular SCFA. Clostridium lentocellum DSM 5427 and the genus Bacteroides were selectively enriched, and these microbial taxa dominated in anaerobic sludge-inoculated cellulose-fed reactors; these taxa were strongly correlated with acetic acid, caproic acid, and enanthic acid production. On the other hand, propionic acid production was strongly related to the abundance of Prevotella ruminicola, Fibrobacter succinogenes, and members of the family Rikenellaceae. Further investigations at the molecular level (metagenome, metatranscriptome, and proteome) are suggested to expand current knowledge and better understand the microbiological factors that dictate the fermentation of cellulosic material within the context of the carboxylate platform. By expanding this understanding, microbiome shaping methods could be designed and evaluated to optimize and scale-up alternative bioprocessing approaches.
Keywords: bioenergy; microbiome; waste valorization; carboxylate platform; anaerobic digestion; short chain fatty acids